2021
DOI: 10.1021/acs.jproteome.0c00995
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Vampire Bat (Desmodus rotundus) Serum Proteome: A Resource for Identifying Immunological Proteins and Detecting Pathogens

Abstract: Bats are increasingly studied as model systems for longevity and as natural hosts for some virulent viruses. Yet the ability to characterize immune mechanisms of viral tolerance and to quantify infection dynamics in wild bats is often limited by small sample volumes and few species-specific reagents. Here, we demonstrate how proteomics can overcome these limitations by using data-independent acquisition-based shotgun proteomics to survey the serum proteome of 17 vampire bats (Desmodus rotundus) from Belize. Us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 117 publications
(200 reference statements)
0
26
0
Order By: Relevance
“…In addition to enhanced excretion, a previous study found that vampire bats limit gastrointestinal iron absorption by increased expression of hepcidin, a factor that inhibits intestinal iron absorption 47 . Furthermore, iron-storing ferritin genes are expanded in the common vampire bat genome 21 and these bats have high levels of iron-binding RFESD in the serum proteome 54 . Thus, limited iron absorption (mediated by increased hepcidin expression), a higher capacity for iron storage (mediated by ferritin and RFESD), and enhanced iron excretion (mediated by inactivating the inhibitory factor REP15) help vampire bats to cope with their iron-rich diet.…”
Section: Loss Of Rep15 and Enhanced Iron Excretionmentioning
confidence: 99%
“…In addition to enhanced excretion, a previous study found that vampire bats limit gastrointestinal iron absorption by increased expression of hepcidin, a factor that inhibits intestinal iron absorption 47 . Furthermore, iron-storing ferritin genes are expanded in the common vampire bat genome 21 and these bats have high levels of iron-binding RFESD in the serum proteome 54 . Thus, limited iron absorption (mediated by increased hepcidin expression), a higher capacity for iron storage (mediated by ferritin and RFESD), and enhanced iron excretion (mediated by inactivating the inhibitory factor REP15) help vampire bats to cope with their iron-rich diet.…”
Section: Loss Of Rep15 and Enhanced Iron Excretionmentioning
confidence: 99%
“…In addition to enhanced excretion, a previous study found that vampire bats limit gastrointestinal iron absorption by increased expression of hepcidin, a factor that inhibits intestinal iron absorption ( 28 ). Furthermore, iron-storing ferritin genes are expanded in the common vampire bat genome ( 17 ), and these bats have high levels of iron-binding RFESD (Rieske Fe-S domain containing) in the serum proteome ( 34 ). Thus, limited iron absorption (mediated by increased hepcidin expression), a higher capacity for iron storage (mediated by ferritin and RFESD), and enhanced iron excretion (mediated by inactivating the inhibitory factor REP15 ) help vampire bats cope with their iron-rich diet.…”
Section: Resultsmentioning
confidence: 99%
“…Looking beyond gene regulation as the primary molecular process of interest, genomic (Blanchong et al, 2016;Longo et al, 2014), epigenomic (Bandyopadhaya et al, 2016;Garcia et al, 2019), proteomic (Heck & Neely, 2020;Horvatić et al, 2016;Neely et al, 2021), and metabolomic methods are also highly relevant to the study of host-pathogen interactions and wildlife disease outcome. For example, genomic methods commonly used to parse organismal adaptation to environmental stressors, such as genome-wide association mapping and selection scans (Brennan et al, 2018;Elbers et al, 2018;Reid et al, 2016), can identify loci that are under selection due to pathogen pressure (Alves et al, 2019;Auteri & Knowles, 2020;Gignoux-Wolfsohn et al, 2021;Gupta et al, 2020;Schwensow et al, 2020).…”
Section: Considering Other Study Designs and Molecular Methodsmentioning
confidence: 99%